Perempuan−Perempuan di Industri Gula Surakarta Abad XIX−XX - Pratika Rizki Dewi (Lembaran Sejarah, 2020)
The role of adult women in Javanese society had closely been associated by public view to domestic affairs. Yet, this view slightly changed in the late nineteenth century. Adult women played a crucial economic role in the job market of the sugar industry in the Surakarta Regency in Central Java, which reached its peak at the turn of the twentieth century. This article shows that many adult women in Surakarta were involved in the blooming sugar industry in Surakarta between 1890s and 1930s because of economic necessity: they served as breadwinners to their families. These women participated either directly by becoming blue collar workers at the sugar industry, or indirectly by selling daily goods taking advantage of the small market thus created by the blossoming of the sugar factory. However, the 1929 Great Depression devastated this business and left the women workers jobless and in poverty. As a result, many of them returned fully the domestic role.